Analisis Faktor-Faktor Yang Mempengaruhi Kecenderungan Kecurangan Akuntansi (Studi Empiris pada Dinas Kota Surakarta) - Ardiana, Wenny, Drs. Muhammad Abdul Aris, M.Si (2016)
This research is intended to analyze the effect of the internal control, compliance of accounting rules, information asymmetry, organizational commitment, organizational culture and unethical behavior of the tendency of accounting fraud in Surakarta city agencies. The population in this research are all finance officer in Surakarta city agencies. The sampling method was done by using purposive sampling according to criteria that have been determined.The number of samples collected as many as 50 finance officer. This research uses multiple linear regression analysis mode. The result of this research showed that the variables of internal control, compliance of accounting rules, information asymmetry, organizational commitment, organizational culture and unethical behavior have significantly effect the tendency of accounting fraud.